Stylistic Features of Comment in Arabic Blogosphere - Zaynullin, Gabdulzyamil G.; Khabibullina, Alfiya M. (Journal of History Culture and Art Research, 2017)
One of the most important issues in the study of the functioning of the Internet language is the definition of the features of each Internet genre presented in online communication, taking into account the linguocultural features of the language in question. This paper studies the genre of the Internet comments of the Arabic-speaking blogosphere and reveals its stylistic features. The most common goal of the comment is gratitude, followed by praise. We created a corpus of comments from blogs of various subjects, and then conducted the tagging, having identified the group to which we attributed a comment, depending on the subject and the communicative goal. With the help of the Lexico 3 software, the most frequent lexical units were identified, the lexical features of the comments were described, the main one being the widespread use of religionyms, and the relationship between the blog subject and the stylistic characteristics of communication was revealed. The article traces the correlation between the literary and colloquial functional style in the comments, and also draws a conclusion that the comments are of a conversational, informal character. The main devices of expressiveness that are characteristic for both network and pre-network communication were revealed, and the tendency of the analysts to observe in the comments a stable three-part composition (greeting, message, final formula). The influence of traditional Arabic rhetoric, as well as the epistolary genre, was preserved. The results of the paper can be used when studying other genres of Internet communication in Arabic and in comparative studies to create the linguistic software.